Keterbukaan Diri dan Kemampuan Pemecahan Masalah - Aris Setiawan (Ilmu Psikologi Universitas Yudharta Pasuruan)
Phase in teenager is a phase of development that is difficult to resolved because these developments are not only physical but also psychic who are building their personality to be more mature, and developments in social aspects requires himself to learn to establish relationships with others in their community, with expectations a teenager can solve every problems. The purpose of this study is to find out whether there is a relationship, between self-disclosure with the ability to solve problems in teenager. The subjects of this study were MA HM Tribakti students, that use 78 students. Data collection uses self-disclosure scale and problem solving ability scale. The results showed, that there is a relationship between self-disclosure and problem-solving abilities in teenagers, with the results of the regression analysis obtained the price F count = 5050 and p = 0.026.